SOCIO-CULTURAL BINOCULARS VIEW OF TELEMEDICINE IN SUB-SAHARAN AFRICA: POTENCY, PROSPECT, DEFECT AND DANGER (American International Journal of Biology and Life Sciences, 2021)
Sub-Saharan Africa has experienced unprecedented technological advancement, just like several other regions of the world. This improvement in technology lends credence to the proliferation of android mobile phones, laptops computers and the Internet facilities that enhance interaction on the social media which in turn generates momentous alterations in the ways the residents of the region construct their daily lives. From epidemiological perspective as well as the viewpoint of change and development, via these information technologies, rendering health-related care and services to the residents in the remote places of the region and gaining access to vital information that prompts prevention and control of diseases are now feasible unlike before the advancement. Therefore, telemedicine symbolizes a health innovation in the region. In the light of this, this paper systematically reviewed the extent to which telemedicine has gained acceptance among the residents of the region; and the socio-cultural factors and practices that promote and decelerate the general acceptance of telemedicine in the region. To accomplish the objective, the review was done meta-analytically and meta-synthetically to explore recent relevant studies. The paper discovered that reduction in the cost of gaining access to health information, harnessing online health and medical services, are among the benefits derived from telemedicine while fake online information, impoverished network service delivery, financial incapacity, theft, technical faults, underutilization of the technology devices and cyber-crime are among the factors that militate against wide acceptance of telemedicine in the region.